Effects of electronic excitation on cascade dynamics in nickel–iron and nickel–palladium systems. (September 2017) - Zarkadoula, Eva; Samolyuk, German; Weber, William J.
Abstract: Using molecular dynamics simulations and the two-temperature model, we provide a comparison of the surviving damage from single ion irradiation events in nickel-based alloys, for cascades with and without taking into account the effects of the electronic excitations. We find that including the electronic effects impacts the amount of the resulting damage and the production of isolated defects. Irradiation of nickel–palladium systems results in larger numbers of defects compared to nickel–iron systems, with similar numbers of isolated defects. We additionally investigate the mass effect on the two-temperature model in molecular dynamics simulations of cascades. Graphical Abstract: